ANALISIS KINERJA KEUANGAN DENGAN EVA DAN MVA PADA PERUSAHAAN TELEKOMUNIKASI PERIODE 2015-2020 - Sari Yana Siregar Siregar; Titin Agustin Nengsih; Erwin Saputra Siregar (Manajemen Keuangan Syariah, 2022)
This study aims to determine whether EVA and MVA provide additional funds for funders and whether EVA and MVA affect the stock price of the telecommunications company. This study uses a quantitative descriptive method. The population in this study were all telecommunications companies and the data analysis tool used was the classical assumption method with multiple linear regression analysis, coefficient of determination, t-test and F-test. The results of this study indicate that: EVA and MVA has no effect on the stock price variable of Telecommunication companies based on the results of the t-test. Based on the f-test shows that there not is an influence between EVA, MVA on stock prices if analyzed together. The result of R2 is 16.7%, the variation in stock prices can be explained by the two independent variables, namely EVA and MVA, while the rest is explained by other variables outside the regression model.